Service Innovation in Elderly Housing The Case of ConceptLiving™ - CHIVILI, SABRIE KOCH (My University, 2019)
Recently, elderly housing in Sweden is problematic because, it does not fulfil the customer needs and expectations. This means there is need for improvement which requires a service innovation in the elderly housings. The purpose of this thesis is to enlarge the understanding and knowledge of the service innovation in the elderly housing. In the context of the research, initially the problems in the existing situation of elderly housings are examined. Regarding those problems, the research also investigates features of service innovations in the housing services for the elderly. This thesis is therefore intended to scrutinize the service innovation process in the elderly housing through a particular single case study. Since the thesis aims to indicate in-depth knowledge about a specific service innovation and a comprehensive summary of the case, a qualitative single case study approach was applied. During the research, data has been collected from literature, lecture presentations and semi-structured interviews. The interviews were conducted with four key persons of the case and three prospective customers of the ConceptLiving™ concept to comprehend perspectives about the existing state of elderly housing market, the concept, the service innovation process, idea generation phase, customer aspect, stakeholder involvement, intellectual property concerns and future insights about the service concept. The findings of the research showed that administrative & economic problems, personal problems and limited service options occur in the elderly housing market and to solve that, customer-centric, value-added, municipality-supported, need-based and technology-oriented housing concepts can be provided to elderly people. It is obvious that each service innovation has a unique process where the stakeholder and customer involvement appear from the phase of developing the idea. Lastly, idea development, intellectual property, profitability of the concept, common values and culture, communication and collaboration with stakeholders and customer aspect are important factors to consider during the process of service innovation.
Keywords: Samhällsbyggnadsteknik; Civil Engineering